The Aggregate Effects of the Hartz Reforms in Germany - Matthias S. Hertweck; Oliver Sigrist (University of Basel, Center of Business and Economics (WWZ), 2013)
This paper quantifies the impact of the Hartz reforms on matching efficiency, using monthly SOEP gross worker flows (1983-2009). We show that, until the early 2000s, close to 60% of changes in the unemployment rate are due to changes in the inflow rate (job separation). On the contrary, since the implementation of the reforms in the mid-2000s, the importance of the outflow rate (job finding) has been steadily increasing. This indicates that matching efficiency has improved substantially in recent years. Results from an estimated matching function — pointing to efficiency gains of more than 20% — corroborate this finding.
Keywords: E24; E32; J63; J64; 330; SOEP gross worker flows; Hartz reform; matching efficiency; unemployment fluctuations; Arbeitsmarktreform; Beschäftigungseffekt; Arbeitslosigkeit; Dauer; Matching; Deutschland